Lateral motion of a droplet impacting on a wettability-patterned surface: numerical and theoretical studies. Issue 3 (21st November 2020) - Zhang, Tongwei; Wu, Jie; Lin, Xingjian
Abstract : A general parameter of effective retraction area has been established to connect the wettability patterns with droplet lateral motion. Abstract : Surfaces with nonuniform wettability have attracted much attention recently due to their academic significance and applications in droplet lateral motion. In this study, numerical simulations and theoretical analyses are conducted to investigate the dynamic behaviors of a droplet impacting on a wettability-patterned surface, in which the superhydrophobic substrate is decorated with a hydrophilic pattern. An improved diffuse interface method coupled with the adaptive mesh-refinement technique and Kistler dynamic contact angle model is adopted to capture the interfacial evolution. After the validation of the numerical method, the dynamic mechanisms of impacting droplets are explored by analyzing the variation of the contact line and velocity profile. Then, systematic simulations are conducted using hydrophilic patterns with different geometric parameters. And the parameter of effective retraction area S is introduced to quantify the wettability patterns. On this basis, the general rules between the patterns and droplet lateral motion are established, and the design principles of hydrophilic patterns are obtained. The numerical results indicate that arc-shape hydrophilic patterns are more appropriate for realizing the droplet lateral motion, which can produce a larger lateral velocity and less residual liquid. In addition, the relevant motion parameters of the droplet are predicted more accurately by using the previous theoretical method. And the mechanism of energy transformation and dissipation is further revealed. Moreover, a simple and practical model is proposed to predict the lateral velocity using the effective retraction area.